Investigation on the aromaticity of 1,3,4-thiadiazole-2-thione and its oxygen analogs including their tautomeric forms - ERDEM, SAFİYE (ELSEVIER SCIENCE BV, 2005)
The aromaticity of 1,3,4-thiadiazole-2-thione and its oxygen analogs including their tautomeric forms, and 1,3,4-thiadiazole, 1,3,4-oxadiazole, furan, thiophene, cyclopentadiene, the cyclopentadienyl anion and the cyclopentadienyl cation has been examined by harmonic oscillator measure of aromaticity (HOMA), aromatic stabilization energy (ASE), differential heat of hydrogenation (Delta Delta HH), and nucleus independent chemical shifts (NICS (0)), calculated at the HF/6-31G**, B3LYP/6-31G**, B3LYP/6-311G**, and B3LYP/6-311 + +G** levels. A principal component analysis (PCA) of the data set generated from these aromaticity results has been presented and compared with similar analyses in the recent literature. It has been shown that aromaticity is at least a two-dimensional phenomenon, independent of the level of the computational method employed. We observed that the sulfur-containing heterocyclic compounds are more aromatic than their oxygen analogs according to geometrical aromaticity measurements. In addition, our calculations of the energies of the tautomeric forms showed that the carbonyl and thiocarbonyl tautomers are more stable than the hydroxy and mercapto forms, which is in good agreement with the experimental findings in the literature. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: hetero-aromatic tautomerism; harmonic oscillator measure of aromaticity; aromatic stabilization energy; nucleus independent chemical shifts; principal component analysis; PI-ELECTRON SYSTEMS; 5-MEMBERED HETEROCYCLES; MOLECULAR-STRUCTURE; RESONANCE ENERGY; DFT CALCULATIONS; DERIVATIVES; 2-ARYL-DELTA(2)-1,3,4-OXADIAZOLINE-5-THIONES; 1,3,4-OXADIAZOLE-2-THIONE; 1,1-DIOXIDE; MODEL